Influence of accounting information systems and internal audit on fraudulent financial reporting - Winwin Yadiati, Sri Mulyani, Erlynda Kasim,; Umar, Haryono (Opción, 2019)
This study examines whether accounting information systems, internal audits, and corporate culture factors affect fraudulent financial reporting and the activities of corporate sustainability. This study was conducted in banks in Indonesia, using structural equation modelling (SEM). This model is based on a covariant known as Based Structural Equation Modeling (CBSEM). The results showed that accounting information systems, internal auditing, and corporate culture significantly affect financial reporting fraud. Similarly, Accounting and Corporate Culture Sustainability have a positive effect on companies. Fraudulent Financial Reporting also negatively affects corporate sustainability. In conclusion, this study fails to prove that Internal Auditing affects Corporate Sustainability.